Does mental health literacy influence help-seeking behavior in medical students? - Nandini Amithya Pramesi Lumaksono; Pudji Lestari; Azimatul Karimah (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: Medical students are experiencing uncertainty in finding the appropriate help for their mental health problems. When they finally decide to seek help, some of them are already in a mental crisis. The suitable indicator for early identification of mental disorder is mental health literacy. Mental health literacy also functions as a tool to decrease stigma towards people with mental illness and to improve help-seeking behavior. The purpose of this study is to determine the influence of mental health literacy to help-seeking behavior and to describe mental health literacy and help-seeking behavior of the medical students.Methods: The study design was observational analytical. Participants filled demographic data and answered questionnaire via an online file sharing platform. The questionnaires used in this study were Mental Health Literacy Scale (MHLS) and Attitudes Toward Seeking Professional Psychological Help Short Form (ATSPPH-SF). The influence of mental health literacy to help-seeking behavior was analyzed using logistic regression analysis. Results: The respondents were 60 medical students. No differences of literacy and attitude were found across the admission years. Overall, the students had good literacy and attitude. Students showed lower scores in the MHLS attributes containing ideas about self-treatments, confidentiality, social distance, and reliance on self. Being literate in the total score of MHLS did not influence on having a good attitude in ATSPPH-SF (p=0.303). Only by being literate in attitudes that promote recognition and help-seeking, the students showed a good attitude in ATSPPH-SF (p-value=0.027). Conclusion: There was no influence on mental health literacy to help-seeking behavior.